INFLUENCE OF COOPERATIVE MEMBERSHIP PARTICIPATION AMONG SMALL-SCALE WOMEN ENTREPRENEURS IN ODOGBOLU LOCAL GOVERNMENT AREA OF OGUN STATE, NIGERIA - Badejo, A.O.; Adewunmi, O.I.; Adebowale, S.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study investigated the effect of cooperative membership participation among small-scale women entrepreneurs in Odogbolu Local Government Area of Ogun-State, Nigeria. Multistage sampling technique was used to select 100 respondents. Data were collected through a well-structured questionnaire administered and analysed using both descriptive and inferential statistics. The result showed that majority (85%) of the respondents were married, with an average age of 47 years. Majority (92%) of the respondents had formal education, with an average of household size of 5 person as family members. The findings from the regression analysis indicated that four (4) variables in the model were positively significant, while only marital status was negatively significant. Education, marital, business experience, access to loans and marital status were significant at 5%, 5%, 5% and 1% respectively, and determinant factors influenced women entrepreneurs of both their decision to join and their intensity of participation in cooperatives. In addition women participation were constraints by low levels of literacy, lack of advertisements, suspicious low income, poor management, high expenditure incurred, low members’ savings and others to proffered suggested solution to constraints. Conclusively, cooperatives had great impact on women’s livelihoods and promote sustainable economic womens’ empowerment. The study therefore recommended that, small-scale women entrepreneurs should improve on their saving culture. Cooperatives and governments should sensitize women cooperators on marketing strategy for easy marketing improvement for profit maximization. Cooperatives should try to provide credit facilities for women cooperative entrepreneurs at appropriate time. Cooperatives should facilitate livelihood diversifications and supporting formation of social enterprises to cooperatives entrepreneur women.